Validity as a social imperative for assessment in health professions education: a concept analysis. Issue 6 (June 2018) - Marceau, Mélanie; Gallagher, Frances; Young, Meredith; St‐Onge, Christina
Abstract : Context: Assessment can have far‐reaching consequences for future health care professionals and for society. Thus, it is essential to establish the quality of assessment. Few modern approaches to validity are well situated to ensure the quality of complex assessment approaches, such as authentic and programmatic assessments. Here, we explore and delineate the concept of validity as a social imperative in the context of assessment in health professions education (HPE) as a potential framework for examining the quality of complex and programmatic assessment approaches. Methods: We conducted a concept analysis using Rodgers' evolutionary method to describe the concept of validity as a social imperative in the context of assessment in HPE. Supported by an academic librarian, we developed and executed a search strategy across several databases for literature published between 1995 and 2016. From a total of 321 citations, we identified 67 articles that met our inclusion criteria. Two team members analysed the texts using a specified approach to qualitative data analysis. Consensus was achieved through full team discussions. Results: Attributes that characterise the concept were: (i) demonstration of the use of evidence considered credible by society to document the quality of assessment; (ii) validation embedded through the assessment process and score interpretation; (iii) documented validity evidence supporting the interpretation of the combination of assessment findings, and (iv) demonstration of a justified use of a variety of evidence (quantitative and qualitative) to document the quality of assessment strategies. Conclusions: The emerging concept of validity as a social imperative highlights some areas of focus in traditional validation frameworks, whereas some characteristics appear unique to HPE and move beyond traditional frameworks. The study reflects the importance of embedding consideration for society and societal concerns throughout the assessment and validation process, and may represent a potential lens through which to examine the quality of complex and programmatic assessment approaches. Abstract : The authors explore and delineate the concept of validity as a social imperative in the context of assessment in health professions education.